Trifluoromethyl Hydrolysis En Route to Corroles with Increased Druglikeness. Issue 23 (1st May 2021) - Yadav, Pinky; Khoury, Sally; Fridman, Natalia; Sharma, Vinay K.; Kumar, Amit; Majdoub, Mahmoud; Kumar, Anil; Diskin‐Posner, Yael; Mahammed, Atif; Gross, Zeev
Abstract: Heme‐like metal‐chelating macrocycles, including expanded and contracted porphyrins, are of everlasting interest as drug candidates for numerous diseases. Still, all reported corrole derivatives (and most other heme analogues) do not fulfill the most basic standards expected for oral drug administration: a combination of low molecular weight and reasonable water solubility. We now disclose a very straightforward synthetic method that relies on surprisingly facile trifluoromethyl hydrolysis for gaining access to a new class of corroles that do satisfy all druglikeness criteria. The relevance is briefly exemplified for the iron corroles by demonstrating the ability to affect their association with plasma proteins and their performance for catalase‐like decomposition of hydrogen peroxide. Abstract : Corroles substituted with only two or three carboxylic acid groups were obtained from readily available starting materials through a novel pathway (see scheme). These macrocycles and the corresponding metal chelates fulfill all the criteria of druglikeness and have potential for both bioimaging and therapy.